ASUHAN KEPERAWATAN KELUARGA TN. J KHUSUSNYA NY. K DENGAN DIABETES MELITUS TIPE II DI RT 04 RW 07 KECAMATAN LIMO, KOTA DEPOK - Amelia Eka Putri (2023)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia. The onset of the disease is caused by damage to pancreatic beta-cells (insulin-producing organs) which causes disruption of the secretion process or insulin work. The purpose of the research is to implement nursing care for clients with diabetes mellitus. This research uses a case study which is part of the research methodology where the subject matter of a researcher is required to be more thorough and careful, and uses family assessment. The results of the case study that has been conducted on the family of Mr. J, especially Mrs. K, are obtained. J Specifically Mrs. K found that the client experienced ineffective health maintenance problems related to the family's inability to recognize the problems of family members with DM and instability of blood glucose levels related to the family's inability to care for, increase or improve family health resolved with reduced complaints and blood sugar levels in the normal range with GDS monitoring. The conclusion of the case on Mrs. K is that nursing problems can be resolved as expected with regular care. Suggestions that can be given are that the family becomes a supporting motivator for the client's health and can maintain a healthy lifestyle together.